Genetic predisposition to Helicobacter pylori-induced gastric precancerous conditions - Hishida, Asahi (Baishideng Publishing Group Co., Limited, 2010)
Gastric cancer is the most common malignancy of the gastrointestinal tract in East Asian populations and the second most frequent cause of cancer-related mortality in the world. While previous studies have investigated the genetic factors involved in gastric carcinogenesis, there still exist relatively few studies that have investigated the genetic traits associated with the risk of gastric precancerous conditions. In this paper we will review the biology and genetic polymorphisms involved in the genesis of gastric precancerous conditions reported to date and discuss the future prospects of this field of study. The associations of gastric precancerous conditions with polymorphisms in the cytotoxin-associated gene A-related genes (e.g. PTPN11 G/A at intron 3, rs2301756), those in the genes involved in host immunity against Helicobacter pylori (H. pylori) infection (e.g. TLR4 +3725G/C, rs11536889) or polymorphisms of the genes essential for the development/ differentiation of the gastric epithelial cells (e.g. RUNX3 T/A polymorphism at intron 3, rs760805) have been reported to date. Genetic epidemiological studies of the associations between H. pylori-induced gastric precancerous conditions and other gene polymorphisms in these pathways as well as polymorphisms of the genes involved in other pathways like oxidative DNA damage repair pathways would provide useful evidence for the individualized prevention of these H. pylori-induced gastric precancerous conditions.